How did COVID-19 pandemic impact on healthy behaviours among Polish professionally active physiotherapists aged 20-50? - Agnieszka Gołuchowska; Marta Balcerzak; Anna Lipert (BMC, 2024)
Abstract Background Due to the introduction of a number of changes to the health care system and the work nature of medical staff, theCOVID-19 pandemic still pose a public health challenge. The objective of the study was to characterize the health behaviours of Polish professionally active physiotherapists during the COVID-19 pandemic. Methods The study included 104 Polish licensed and professionally active physiotherapists in whom health behaviours were assessed using an original questionnaire contained, among others, questions from the Global Physical Activity Questionnaire (GPAQ), the Pittsburgh Sleep Quality Index (PSQI) and the Perceived Stress Scale (PSS), available via social media platforms. Results Among the physiotherapists, 34% worked directly with COVID-19 patients and 49% with those who had survived COVID-19. There were no statistically significant differences in most of the rates of physical activity undertaken by the physiotherapists surveyed (P > 0.05). Men were more likely to report taking up movement-related physical activity than women (P > 0.05). However, they spent more time sitting or lying down on a typical day (P > 0.05). The average time spent on the above-mentioned physical activities was also higher among the male participants than in the group of women (P > 0.05). There was an increase in the proportion of physiotherapists working over 40 h per week, from 29% before the pandemic to 38% during the pandemic. Statistically significant differences were observed for the products constituting the basison which of the diet of the examined physiotherapists was based (P < 0.05). The majority of the respondents reported no problems with falling asleep (p > 0.05). Stress related to the risk of contracting COVID-19, as well as concerns about the health of loved ones were more common and severe in the group of female subjects (P < 0.05). Conclusions During the COVID-19 pandemic, the health behaviours in some physiotherapists changed. Further studies are required to assess whether physiotherapists' health behaviours returned to baseline levels or slightly improved compared to the initial results. Also, it is necessary to introduce health-promoting initiatives that would focus on physiotherapists, support their positive health behaviours and provide special recommendations helping them to maintain health during a pandemic.